(untitled) - Cengel, Yunus A. (New York, 2005)
The text covers the basic principles of thermodynamics, heat transfer and fluid mechanics in a readable manner, with 2-colour graphics throughout. The emphasis is kept on physics and physical arguments in order to develop an intuitive understanding of the subject matter. The text contains sufficient material to give instructors flexibility, and to accommodate their preferences on the right blend of thermodynamics, heat transfer and fluid mechanics for their students.
Keywords: Thermodynamics,Heat,Fluid mechanics,Nhiệt động lực học,Nhiệt,Cơ học chất lỏng; Transmission,Truyền dẫn